2015
DOI: 10.1097/sle.0000000000000131
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Pilonidal Sinus Treatment in the Asian Population

Abstract: EPSiT is a minimally invasive and cosmetically favorable procedure. A larger sample size and a longer follow-up is required to determine if it improves healing time and long-term recurrence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 12 publications
2
21
0
Order By: Relevance
“…Of interest, Meinero et al 7 designed a similar minimally invasive treatment to treat pilonidal sinus and obtained good results in 11 consecutive patients. These findings were later confirmed by the experience of Chia et al 31 with 9 consecutive patients.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Of interest, Meinero et al 7 designed a similar minimally invasive treatment to treat pilonidal sinus and obtained good results in 11 consecutive patients. These findings were later confirmed by the experience of Chia et al 31 with 9 consecutive patients.…”
Section: Discussionsupporting
confidence: 52%
“…A new endoscopic treatment for pilonidal sinus has been proposed. 6,7,31 We designed VAAPS, which is based on the concept of complete removal by ablation of the sinus with a minimal surgical wound. Whereas in the conventional surgical treatment an elliptical wedge of skin and subcutaneous tissue is created to remove the sinus and its lateral tracks, the theory of our new treatment is to create a minimal elliptical wedge of the subcutaneous tissue, including all the inflamed tissue and debris, leaving the overlying skin intact.…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive treatment has many advantages. Several studies have shown that the period off work after EPSiT is shorter than after more extensive operations . Such patients also tend to experience less pain and better quality of life after endoscopic operation for pilonidal sinus than after classic flap surgery .…”
Section: Discussionmentioning
confidence: 99%
“…EPSiT is shorter than after more extensive operations [13][14][15][16][17][18]. Such patients also tend to experience less pain and better quality of life after endoscopic operation for pilonidal sinus [11] than after classic flap surgery [19].…”
Section: Discussionmentioning
confidence: 99%
“…No sig nif i cant com pli cations have been re ported with the ad van tage of less pain and no re cur rence in the first six months of ther apy 15 . The aes thetic re sults too were better than con ven tional pro cedures 16 .…”
Section: En Do Scopic Pilonidal Si Nus Treat Mentmentioning
confidence: 89%